Pentoxifylline vaginal gel improves sperm motility and vitality in asthenozoospermic males: A randomized, blinded, in vitro study - Trilla, Cristina; Navarro, Lidia; Rius, Mariona; Espinós, Juan José (Frontiers in Pharmacology, 2025)
IntroductionIn this study, we aimed to evaluate the in vitro effects of a 4% pentoxifylline-containing vaginal gel (PKB171 4%) on sperm motility and vitality in samples from asthenozoospermic males, compared with its placebo vaginal gel.MethodsThis was a prospective, blinded, placebo-controlled study conducted at Fertty Clinic, Barcelona, Spain. Thirty-two semen samples from men with asthenozoospermia were randomized for treatment with either PKB171 gel containing 4% of pentoxifylline or a PKB171 placebo gel. Sperm motility and vitality were assessed at baseline and at three points following exposure: immediately (T0), after 45 min (T45), and after 180 min (T180). The evolution of sperm motility and vitality over time after exposure was compared between the groups.ResultsAt T45, the group treated with PKB171 4% showed an increase in progressive motility compared with T0. Progressive motility was significantly higher in the PKB171 4% group than in the placebo group (35.3% vs. 28.9%, p = 0.035). Compared to baseline, the PKB171 4% group experienced only a 1% decline in progressive motility, whereas the placebo group exhibited a 10.8% reduction (p = 0.011). Vitality was also more preserved in the PKB171 4% group, with significantly lower vitality decline at T45 and T180 than in the placebo group. Although motility and vitality decreased over time in both groups, the decline was consistently less severe in samples treated with the PKB171 4% gel.DiscussionThe PKB171 4% gel significantly improves progressive motility and preserves sperm vitality in sperm samples from asthenozoospermic males. These promising in vitro findings require further clinical investigation to confirm the potential benefits in infertile couples with male infertility.